Mining and metallurgical complex of Ukraine: current state and development prospects - O. E. Riabtseva (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The article is devoted to the analysis of the state of the second most important industry for the Ukrainian economy – the mining and metallurgical complex. The purpose of the article was analytical substantiation of the causes and consequences of problematic functioning of enterprises of the mining and metallurgical complex of Ukraine. Iron ore raw materials are one of the few types of mass export products in Ukraine. The analyzed indicators of individual companies in the industry show that the decline in MMC has not been overcome, despite some improvement in recent months. The dynamics of the number of personnel at individual mining enterprises in the period from January 2022 to June 2023 were studied, that is, a comparison of current with pre-war indicators. In addition, the dynamics of wages for the specified period at mining, metallurgical and pipe enterprises were analyzed. The most significant negative impact caused by the war was ground by the loss of large metallurgical plants in Mariupol and the blockade of Black Sea ports through which the products of metallurgical enterprises were exported. At the same time, one of the most significant internal negative factors is the lack of proper modernization of production and, as a consequence, the loss of competitive advantages. The conducted analysis indicates an unstable situation in metallurgy. Possible force majeure circumstances can radically change expectations, therefore protection of one of the most important industries in Ukraine's economy should become one of the main tasks of the state during martial law.